ACTIVITIES OF INTERNATIONAL ORGANIZATIONS IN THE SPHERE OF PREVENTION AND LIMITATION OF EMERGENCY SITUATIONS IN THE ARCTIC REGION - Vladimir A. Gavrilenko; Inga V. Goloveiko; Stanislav B. Nemchenko (Russian Studies in Law and Politics)
Relevance. The relevance of the ongoing scientific work is due to the need to develop reasonable proposals to improve the legal regulation of international cooperation in the field of emergency prevention and response in the Arctic.